KARAKTERISASI KARBON AKTIF DARI SERBUK KAYU NANGKA LIMBAH INDUSTRI PENGGERGAJIAN DAN EVALUASI KAPASITAS PENYERAPAN DENGAN METHYLENE BLUE NUMBER - Tintin Mutiara; Rizki Fajri; Intan Nurjannah (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
In Indonesia the yield of sawmill industry waste is about 50-60%, the 15 up to 20% of this waste consists of wood powder and so far there is not an optimum utilization. This experiment was conducted in order to process wood powder of jackfruit into activated carbon as adsorbent of heavy metals in the wastewater treatment. Activated carbon processing was performed at various temperature. Instrumental analysis was carried out with SEM-EDX and FTIR to determine the characteristics of the activated carbon. The size of pore diameter was measured with SEM, resulted macropore surface pores. Infra red spectra showed nitrile triple bond C≡N and hidroxyl bond O-H. Based on those bonds, activated carbon from jackfruit could be an adsorbent of acid gas and water. The best conditions resulted adsorption capacity of methylene blue 55 mg/g with percent removal 40.70%